Work overload, role conflict and emotional distress as predictors of burnout among police cadets in Nigeria - Adebusuyi, Adeola Samuel (International journal of police science & management, 2023)
Burnout has been investigated among different categories of human service professionals and students. However, it has not been investigated among police cadets simultaneously combining university education and police training. Hence, this study investigated the causes of burnout among the Nigeria Police Academy (POLAC) cadets in Nigeria. Specifically, using Frone et al.’s integrative model of the work–family interface, I investigated the antecedent influence of work overload (academic and police), role conflict (academic and police) and emotional distress (academic and police) on burnout among cadets [Frone MR, Yardley JK and Markel KS (1997) Developing and testing an integrative model of the work–family interface. Journal of Vocational Behavior 50(2): 145–167]. The study is cross-sectional, with a sample size of 300, and the data were analysed using regression path analysis. The result showed that academic and police work overload led directly to burnout. In addition, academic work overload led indirectly to burnout through academic role conflict and emotional distress, whereas police work overload led to burnout through police-emotional distress. Furthermore, academic-to-police role conflict led indirectly to burnout through academic-emotional distress. This study extends extant literature on the antecedents of burnout in police organizations. It also suggests important implications such as revising the curricula to make them more manageable for the cadets and the need to be stringent with the admission process into the academy.